Dynamic simulation and characteristics analysis of traffic noise at roundabout and signalized intersections. (June 2017) - Li, Feng; Lin, Yushan; Cai, Ming; Du, Canyi
Highlights: A vehicle noise emission model considering the acceleration effect is established. Traffic noise near intersections is simulated and measured. The upper limit of traffic noise near intersections is discussed. Abstract: Traffic noise prediction is an important topic for traffic environment planning in cities. The complex traffic flow at road intersections makes the prediction of traffic noise challenging. In this paper, a dynamic traffic noise simulation method based on microscopic traffic simulation is used to study the traffic noise near roundabout and signalized intersections. A vehicle noise emission model that considers the effect of acceleration is established using an experimental method. The accuracy of the model is verified by comparison with measured data. Traffic noise near roundabout and signalized intersections under different traffic volume levels is simulated, and the results are compared. Some significant relations between traffic noise and traffic volume are obtained, and the mechanisms are analyzed. The results show that traffic noise reaches an upper limit when traffic is saturated, and the noise energy contribution of the exit lane is far greater than that of the entrance lane.